Do confident CEOs increase firm value under competitive pressure?. Issue 17 (7th October 2021) - Cho, Kyumin; Kim, Hyeong Joon; Mun, Seongjae; Han, Seung Hun
ABSTRACT: Traditional studies show that CEOs' overconfidence can mitigate underinvestment problem that occurs due to risk-aversion. To extend this argument, we investigate whether investment by overconfident CEOs always increases firm value. Theoretically and empirically, we show that investment by overconfident CEOs and firm value is positively related for firms in more competitive industries. For firms in less competitive industries, the relation is insignificant. Our findings suggest that CEOs' overconfidence can be a desirable managerial trait for shareholders under certain conditions.